The role of the artist in the Maya society in the late classical period based on epigraphic analysis of the signatures of scribes and sculptors - Jagodziński, Kajetan (Studia Europaea Gnesnensia, 2019)
The role of the artist in the Maya society in the late classical period based on epigraphic analysis of the signatures of scribes and sculptors